2008
DOI: 10.1038/sj.bjc.6604545
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumour cells in peripheral blood with an automated scanning fluorescence microscope

Abstract: We have developed an automated, highly sensitive and specific method for identifying and enumerating circulating tumour cells (CTCs) in the blood. Blood samples from 10 prostate, 25 colorectal and 4 ovarian cancer patients were analysed. Eleven healthy donors and seven men with elevated serum prostate-specific antigen (PSA) levels but no evidence of malignancy served as controls. Spiking experiments with cancer cell lines were performed to estimate recovery yield. Isolation was performed either by density grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 15 publications
1
71
0
1
Order By: Relevance
“…The technology is still in the proof-of-principle stage but is showing promise in that it can be combined with FISH to further characterize CTCs. The range of CTC detection is similar to that of CellSearch [12].…”
Section: Current Utility Of Circulating Tumor Cells: Enumerationsupporting
confidence: 52%
“…The technology is still in the proof-of-principle stage but is showing promise in that it can be combined with FISH to further characterize CTCs. The range of CTC detection is similar to that of CellSearch [12].…”
Section: Current Utility Of Circulating Tumor Cells: Enumerationsupporting
confidence: 52%
“…Phagocytosis events were detected using the Ikoniscope imaging system (Ntouroupi et al, 2008). Slides are first scanned at low magnification ( Â 10) to detect green label and then revisited at high magnification ( Â 100) to identify red labelled macrophages with 'engulfed' green targets.…”
Section: Monocyte-derived Macrophages For Phagocytosis Assaysmentioning
confidence: 99%
“…An alternative ADCP assay was developed using an automated microscope (Ikoniscope, Ikonisys, New Haven, CT, USA) (Ntouroupi et al, 2008). Target cells and macrophages, stained as described above, were deposited on to a poly-l-lysine coated slide, fixed with 2% formaldehyde.…”
Section: Monocyte-derived Macrophages For Phagocytosis Assaysmentioning
confidence: 99%
“…The samples were analyzed with the Ikoniscope robotic fluorescence microscope imaging system. The results showed that the sensitivity of this method could detect less than one epithelial cell per milliliter of blood, and fluorescence in situ hybridization (FISH) could identify chromosomal abnormalities in these cells (Ntouroupi et al, 2008).…”
Section: Liquid Biopsies In Tumour Diagnosis and Treatmentmentioning
confidence: 98%